IMPROVING TRAINING AND EDUCATION IN CLUSTERS - LESSONS FROM THREE PORT CLUSTERS Improving Training and Education in Clusters - Lessons from Three Port Clusters - Peter W. De Langen (European Regional Science Association (ERSA), 2005)
The quality and availability of labour is essential for the economic performance of clusters. The availability of labour in clusters is superior compared to locations outside clusters, because labour is more mobile in clusters, education services in clusters are better and employees in clusters have a higher willingness to invest in specific skills. These effects arise 'spontaneously', as a result of 'market forces'. Apart, from these effects, in some clusters, firms and governments also actively aim to improve the quality of the labour pool in the cluster. Clusters differ in the extent to which relevant stakeholders manage to invest in the quality of the labour pool. Thus, superior 'organising capacity' is a potential source of competitive advantage of a cluster vis-à-vis other clusters. This paper presents an analysis of these efforts of firms and governments to improve the quality of the labour force in three seaport clusters. The concept of a 'training and education regime' is used to analyse efforts of firms and governments to improve the labour pool. The results of three case studies of port clusters lead to a number of conclusions. First, the assumption that the quality of training and education regime differs substantially per cluster is validated. Second, the presence of a 'regime manager' adds to the quality of Rotterdam's training and education regime. Such an organisation may be effective across countries and clusters. Finally, the presence of leader firms, willing to invest in training and education improves an education regime.
Keywords: 330